Pengaruh Profitabilitas, Leverage, Total Arus Kas dan Ukuran Perusahaan Terhadap Financial Distress Pada Perusahaan Property dan Real Estate Yang Terdaftar di BEI 2021-2023 - Rian Annes Gigs Hutapea; Ikbar Pratama; Linda Lores (Politeknik Ganesha Medan, 2025)
The purpose of this research is to analyze the effect of profitability, leverage, total cash flow, and company size on financial distress in property and real estate companies listed on the Indonesia Stock Exchange as the focus of the research presented in 2021-2023. The research method used in this study is quantitative, this study uses a purposive sampling method. The sample consisted of 81 companies in the property and real estate sector recorded in 2021-2023. The results of the study are that the liquidity variable affects the financial distress variable, the profitability variable does not have a significant effect on financial distress, total cash flow does not have a significant effect on financial distress, and company size does not have a significant effect on financial distress.